Bacteria-induced uroplakin signaling mediates bladder response to infection. - Praveen Thumbikat; Ruth E Berry; Ge Zhou; Benjamin K Billips; Ryan E Yaggie; Tetiana Zaichuk; Tung-Tien Sun; Anthony J Schaeffer; David J Klumpp (PLoS Pathogens)
Urinary tract infections are the second most common infectious disease in humans and are predominantly caused by uropathogenic E. coli (UPEC). A majority of UPEC isolates express the type 1 pilus adhesin, FimH, and cell culture and murine studies demonstrate that FimH is involved in invasion and apoptosis of urothelial cells. FimH initiates bladder pathology by binding to the uroplakin receptor complex, but the subsequent events mediating pathogenesis have not been fully characterized. We report a hitherto undiscovered signaling role for the UPIIIa protein, the only major uroplakin with a potential cytoplasmic signaling domain, in bacterial invasion and apoptosis. In response to FimH adhesin binding, the UPIIIa cytoplasmic tail undergoes phosphorylation on a specific threonine residue by casein kinase II, followed by an elevation of intracellular calcium. Pharmacological inhibition of these signaling events abrogates bacterial invasion and urothelial apoptosis in vitro and in vivo. Our studies suggest that bacteria-induced UPIIIa signaling is a critical mediator of bladder responses to insult by uropathogenic E. coli.